Globalization, platform work, and wellbeing-a comparative study of Uber drivers in three cities: London, Helsinki, and St Petersburg - Meri Koivusalo; Arseniy Svynarenko; Benta Mbare; Mikko Perkiö (BMC, 2024)
Abstract Background Globalization of platform work has become a challenge for wider social and employment relations and wellbeing of workers, yet on-location work remains governed also by local regulatory context. Understanding common challenges across countries and potential for regulatory measures is essential to enhance health and wellbeing of those who work in platform economy. Our comparative study on platform work analyzed concerns of Uber drivers in three cities with a different regulatory and policy context. Methods Drawing from current understanding on employment and precarity as social determinants of health we gathered comparative documentary and contextual data on regulatory environment complemented with key informant views of regulators, trade unions, and platform corporations (N = 26) to provide insight on the wider regulatory and policy environment. We used thematic semi-structured interviews to examine concerns of Uber drivers in Helsinki, St Petersburg, and London (N = 60). We then analysed the driver interviews to identify common and divergent concerns across countries. Results Our results indicate that worsening of working conditions is not inevitable and for drivers the terms of employment is a social determinant of health. Drivers compensated declining pay with longer working hours. Algorithmic surveillance as such was of less concern to drivers than power differences in relation to terms of work. Conclusions Our results show scope for regulation of platform work especially for on-location work concerning pay, working hours, social security obligations, and practices of dismissal.